Cost-Efficient Mixed-Level Covering Designs for Testing Experiments - Akhtar, Yasmeen; Phoa, Frederick Kin Hing (Journal of statistical theory and practice, 2020)
A covering design is a traditional class of experimental plans for hardware and software testing purposes. This paper presents a class of size-optimal covering designs for testing experiments with mixed-level factors. Among all the factors of different levels, one or two factors have a high number of levels while other factors form a full factorial so that all level combinations among factor pairs are “covered” at least once and appeared almost equally frequent. We use the coloring techniques for hypergraphs to construct such near-balanced mixed-level covering designs with the minimum run size.